THE IMPACT OF E-CRM ON CUSTOMER LOYALTY - Subandriyo; Sulivyo L.; Usman B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
This research aims to find out the influence of e-service quality, e-CRM, and e-satisfaction on the e-loyalty of customers of one of the e-malls in Indonesia. Exogenous research variables are e-service quality and e-satisfaction while endogenous research variables are e-CRM and e-loyalty. The sample was taken from 351 respondents who were consumers of e-mall X. Data analysis techniques using SEM PLS. The results showed that all significant hypotheses can be concluded that the influence of e-service quality, e-CRM, and e-satisfaction on e-loyalty of E-mall X customers either directly or indirectly.